TYPES OF PEDAGOGICAL OBSERVATION METHOD AND ITS APPLICATION IN MEDICAL PRACTICE (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article examines the pedagogical observation method as one of the fundamental research and instructional tools in medical education. The study identifies and classifies the principal types of pedagogical observation - structured, unstructured, participant, non-participant, systematic, and naturalistic - and provides a detailed analysis of their theoretical foundations.